Postpartum Haemorrhage in the Developing World A Review of Clinical Management Strategies - Snelgrove, John W. (McGill University, 2009)

(untitled)
The developing world is disproportionately burdened with high rates of maternal mortality. Despite widespread reduction in maternal deaths due to improved antepartum, intrapartum, and postpartum care in developed nations, mortality rates are persistently high in many countries unable to provide advanced medical care. Postpartum haemorrhage accounts for a substantial proportion of maternal deaths in developing countries. This review addresses the clinical management strategies aimed at the prevention and treatment of postpartum haemorrhage that are effective in lowresource settings. The review was conducted by searching the English-language medical literature using MEDlINE (1950 - Feb 2009) and the online search engine Google Scholar. Four relevant strategies were identified in the literature: active management of the third stage of labour (AMSTl), the use of uterotonic agents including misoprostol, accurate measurement of blood loss, and internal and external compression techniques. Despite known intervention options, additional research on effective management strategies and their implementation is needed to address postpartum haemorrhage in countries of the developing world.